Model for optimizing productivity in buffaloes - SETHI, R K; NAGARCENKAR, R (The Indian Journal of Animal Sciences, 2013)
A system model for optimizing buffalo production under wide range of conditions with animals differing in genetic potential for body weights, milk yield, service period and dry period is described. In the moddel genetic potential is specified as the function of standard normal deviate from least-squares constants. Feed and fodder intake is estimated from nutritional equations as a function of growth, maintenance, reproduction and production in terms of DCP, TDN and DM content of the available feeds. Least cost rations estimated through linear programming have been used to estimate multiple regression coefficients for predicting cost of feeding. Data on body weight, milk yield, fat yield, death and replacement rate, sale andpurchase cost, and production and reproduction variables are estimated by the use of least-squarcs constants, regression equations and live tables. The model has been used for simulating buffalo productivity for different female calf rearing policies at varying socio-economic locations in India.